On the Hydrogen-Ion Concentration in the Alimentary Canal of the Coleoptera. - Srivastava, Uma Shanker; Srivastava, P. D. (Contributions to Entomology = Beiträge zur Entomologie, 1961)
1. The hydrogenion concentration of the fore-gut, mid-gut, and hind-gut and blood of sixteen species of Coleoptera, belonging to 12 families has been determined. It ranges from 5.2 to 6.8, 5.4 to 6.8, and 5.3 to 7.0 in the fore-gut, mid-gut and hind-gut respectively. - 2. The total range of pH in the different parts of the alimentary canal is very small, the difference between the maximum and minimum being only 1.2. - 3. On the whole, the alimentary canal may be said to be slightly acidic. - 4. In most cases, there is a close correspondence between the pH of mid-gut and blood. - 5. There does not appear to be any relationship between the feeding habit and pH of the alimentary canal. On the other hand, the pH seems to be related to the group to which an insect belongs. - 6. The existence of different kinds of buffer mechanisms in groups of insects with different pH ranges is inferred.